ROLE COASTUMER SERVICE PT. BANK DANAMON PROVIDE SERVICE TO CUSTOMERS - Hardani, Ninda; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. Bank Danamon Pekanbaru is the bank engaged in banking goods and services that always seeks to prioritize the satisfaction of its customers. The employee on duty and deal directly with the customer in providing services commonly known as customer service that are required to have the ability to serve customers accurately and quickly and have good communication skills. The purpose of this study was to determine the role of customer service as a receptionist, Deskman, salesman, customer relation officer, and communicators in providing services to customers.This study used qualitative research methods. In this case the researchers used purposive sampling technique to sample customer service. The sample set 2 costumer service. While the sample from the customer to use accidental sampling technique. Informants were used for the customer as much as 4 people. In collecting the data, researchers use interviewing techniques, observation. By using key informants as sources of information.The results show is the role of customer service as recepcionis, deskman, customer relation officer, communicators in providing services to customers is to serve quickly and accurately and have a good knowledge and ability, understand the needs of customers, responsible to each customer from start to finish, guarantees the confidentiality of any transaction and provide confidence to customers.Key Words : The role of customer service,service